“Mange af de ting, jeg glæder mig til, er også mange af de ting, der skræmmer mig” - Anne-Louise Karstoft Klein; Anne-Lisbeth Nyvang; Christina Prinds (Tidsskrift for Professionsstudier)
This qualitative study delves into the reflections of eight Danish midwifery students regarding their profession. Despite midwives' pivotal role in maternal care, little attention has been given to understanding the reflections of those preparing to enter this profession. The findings revealed a nuanced interplay of ambivalence, worry, doubt, excitement, and expectations that shaped students' perceptions. Amidst students' apprehensions were also thoughts about resilience. Engaging in dialogue with other newly educated midwives was perceived as a valuable resource by participants.